IMPLEMENTASI VIDEO EXPLAINER SEBAGAI STRATEGI DALAM PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP N 1 SINUNUKAN - Torang Siregar; Suparni; Almira Amir; Anita Adinda (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2024)
Abstract This research aims to determine the results of the implementation of Video Explainer in terms of students' Problem Solving Ability. This research is Classroom Action Research which consists of 2 cycles, each cycle consisting of 2 meetings. The data collection technique is through giving a problem solving ability test. The subjects in this research were 28 students of class IX SMP Negeri 1 Sinunukan. The results of the students' problem solving ability test in the initial test showed that 5 students (17.85%) experienced completeness with an average ability test score of 54.82 in the very low problem solving ability category. In the first cycle, there was a classical improvement as shown by the achievement of 13 students (46.42%) completing the test with an average score of 66.78 in the low category. Implementation continued in cycle II, student test results experienced a classical increase, 25 students (89.28%) completed the results with an average score of 80.23 in the high category. From the results of the tests given, there was an increase from the initial test to cycle II. Thus, it is concluded that implementing explainer videos can improve the problem solving abilities of class IX students at SMP Negeri 1 Sinunukan.